Leukoaraiosis does not impact motor outcomes in Parkinson’s patients post deep brain stimulation - Heather Martin; Rushna Ali; Ashok Sriram; Robert Coleman; Emily Ruether; Hayden Boyce; Morgan L. Maley; Muhib Khan (Clinical Parkinsonism & Related Disorders)
Objectives: We sought to assess the impact of leukoaraiosis (LA) on motor outcomes in Parkinson disease (PD) patients undergoing DBS. We hypothesized that LA is associated with less improvement in motor function in PD patients post-DBS. Methods: We reviewed data of adult patients with PD treated with DBS in a single center between 2012 and 2021. Demographics, risk factors, medications, Hoehn and Yahr scale and Unified Parkinson’s Disease Rating Scale (UPDRS) Motor Score before and after DBS and severity of LA were collected. Simple linear regression (SLR) was used to determine variables of interest to include in the multiple linear regression (MLR). MLR was used to determine independent predictors of motor outcomes (UPDRS) post-DBS including LA as a continuous and dichotomized variable of interest. Results: A total of 90 patients were included in the analysis. Mean age was 65.7 years (±9.7), primarily male (69 %) with a high incidence of young onset PD (29 %), treated with carbidopa/levodopa combination (98 %) and with moderate severity of disease (Hoehn and Yahr Stage 2.0 [2.0, 2.5]). Moderate to severe leukoaraiosis was noted in 26 (32.5 %) patients. SLR revealed age, diabetes and disease severity as predictors of post-DBS motor UPDRS. In adjusted analysis, LA was not an independent predictor of motor outcomes post-DBS either as continuous (β = 0.20, p = 0.77) or dichotomized (β = −0.64; p = 0.77) variable. Conclusion: In conclusion, our data suggests that motor outcomes in Parkinson’s disease patients undergoing deep brain stimulation (DBS) are not impacted by pre-existing leukoaraiosis. Further studies are needed to validate our findings.